Fungsi Bimbingan dan Konseling - Muhammad Faturohman; Titi Sunarti; Ghaisani Al Amah; Ilham Adriansyah; Ilham Mubarok (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2026)
Guidance and counselling are essential services in schools that function to help students develop optimally, both in personal, social, learning, and career aspects. Students often face various problems that can hinder their development and learning process, making planned and continuous guidance and counselling services necessary. This research aims to describe the function of guidance and counselling in assisting student development in the school environment. This research uses a qualitative approach with a descriptive method. The research subjects consist of guidance and counselling teachers or counselors and students as service recipients. Data collection techniques were carried out thru observation and in-depth interviews, which were then analyzed thru data reduction, data presentation, and conclusion drawing stages using source and technique triangulation. The research findings indicate that the functions of guidance and counselling in schools include understanding, prevention, remediation, and development. These four functions are realized thru various services such as orientation, information, study guidance, individual counselling, and group counselling. The implementation of guidance and counselling functions makes a positive contribution to helping students understand themselves and their environment, preventing the emergence of problems, overcoming the problems they face, and optimally developing students' potential. Thus, guidance and counselling services play a strategic role in supporting the holistic educational process in schools.